Quality management system proposal for complex organizations - Purcărea, Anca-Alexandra; Ţigănoaia, Bogdan; Teaha, Corneliu Teofil (Propozyja systemu zarządzania jakością w złożonych organizacjach, 2011)
This paper presents models of Quality Management Systems that are suitable for complex organizations. Normative and excellence Quality Management System solutions are analyzed and a comparison is made. Several comments regarding ISO 9001:2008 international standard are presented in this paper. Finally, a Quality Management System is implemented within a complex organization, Teaha Management Consulting – JW Marriott Grand Offices, Bucharest, Romania and several conclusions and future work are presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 202, s. 79-87
Keywords: quality; management systems; complex organizations; international standards